IMPACT OF MICROFINANCE INSTITUTIONS ON RURAL PROMOTERS (International Journal of Food and Nutritional Sciences, 2022)
The provision of financial services is essential for decreasing poverty. People in poverty can gain control of their lives by having constant access to financial services. Poor individuals who live in insecure circumstances and are challenged by a lack of money, housing, and food may need good management of very small assets in order to survive. They need to be able to invest, save, borrow, and protect their families from risk in order to escape poverty.Poor people can receive modest loans from non-governmental organizations (NGOs) and microfinance institutions like credit unions, receive remittances from relatives working abroad, and safeguard their investments. Poor individuals can start small enterprises if they have access to low quantities of financing at low-interest rates.Present study the profile of the MSMEs in the promoters under the heads like the social-economic conditions, support in rural promoters, and awareness of ruler promoters factor that induced them in promoting the business units are analysed. The socio-economic profile is the criterion, it influences to a great extent the promotion of the unit, and the knowledge about the microfinance institutions by applying tools such as percentage analysis, rank, chi-square test, and one-way ANOVA used in this paper.